Screening For Antimicrobial Activity Of Fungi In Soil Samples Collected From Kubah National Park - Lihan, S.; Choon, Y.K.; Hua, N.K.; Wasli , M.E. (International Journal Of Scientific & Technology Research, 2014)
Antimicrobial agents including antivirals and antibiotics have saved millions of lives all over the world, but these drugs are losing their effectiveness due to the development of resistance of infectious disease agents towards them. The incidence of antibiotic-resistance towards current drugs has been rapidly increasing but fewer new antibiotics are being developed. This study was carried out on soil samples collected from Kubah National Park, Kuching, Sarawak, Malaysian Borneo, in order to discover novel antibiotics produced by soil microbes. Twenty one samples of soils were analyzed for antimicrobial producing fungi. Potential fungal isolates were tested against Escherichia coli, Listeria monocytogenes, Salmonella enteritidis and Klebsiella pneumoniae. Six fungal isolates labeled P550AIa, P550AIb, P550AIc, P550AId, P550AIIa, P550AIIb showed strong antibacterial activity against the test bacteria during the antimicrobial activity screening using agar overlay technique in the preliminary screening and secondary screening. Out of the 6 fungal isolates, 3 isolates P550AIa, P550AIb, P550AIc were selected to undergo antibiotics susceptibility testing and further characterization. The crude extract of the 3 fungal isolates were further characterized by MIC, TLC and bioauthography methods. The isolates showed MIC value and produced inhibition zone compared to the positive control (5×dilutions of penicillin-streptomycin solution). The characteristics of the spores produced by the three fungal isolates matched with the description for Penicillium spp.. Further confirmation by DNA sequencing of isolate P550AIb revealed its identity as Penicillium verruculosum. All the fungal isolates showing antimicrobial activity are potential to be used for producing antimicrobial compound for combating infectious bacterial agents as evidenced in this study.